Determination of 210Po concentration in commercially available infant formulae and assessment of daily ingestion dose. Issue 3 (July 2015) - Prabhath, Ravi K.; Sreejith, Sathyapriya R.; Nair, Madhu G.; Rao, D.D.; Pradeepkumar, K.S.
Abstract: A study has been conducted to estimate the concentration of natural radioactive polonium in commercially available packaged infant food formulae available in Mumbai, India and the corresponding daily dose normalized based on its shelf life. Eleven most popular international brands of infant formulae were sourced from market and three aliquots from each sample were analysed for concordant results. Autodeposition method onto a silver planchet from hot dilute acid solution followed by alpha spectrometry was performed for estimation of polonium. Radiochemical recovery was ascertained by the addition of 209 Po tracer. Radiochemical recovery of 209 Po tracer was ranged from 14.7 to 98.1 %. The 210 Po concentration in the samples was in the range of 0.08–0.23 Bq kg −1 on measured date and the corresponding daily dose, calculated on normalized date which is at mid-point of the shelf life of the sample, was ranged from 0.04 to 0.89 μSv d −1 as per the recommended daily consumption. The annual committed effective dose estimated based on the average of daily dose was found to be 150 μSv.